Oral administration of l-citrulline alters the vascular delivery of substances to rat skeletal muscles - Sho Miyatake; Kazuo Hino; Goro Ebisu; Satoshi Fujita (Biochemistry and Biophysics Reports, 2021)
Vascular endothelial function deteriorates with age and disease, and the production of vasodilator factors like nitric oxide (NO) decreases. The free amino acid l-citrulline increases vasodilation and blood flow through increased NO production. We examined the effects of oral l-citrulline administration on vascular delivery of substances to skeletal muscles. In Experiment 1, following oral l-citrulline administration and subsequent intravenous Evans blue dye (EBD) administration to rats, EBD levels delivered to skeletal muscles were measured after 60 min. In Experiment 2, plasma concentrations of amino acids and NOx, an indicator of vasodilation, were measured over time after oral l-citrulline administration. In Experiment 3, we measured EBD levels in skeletal muscles of streptozotocin-induced type 1 diabetic rats following l-citrulline administration. In these experiments, EBD levels in the soleus muscle were higher in the l-citrulline group than in the control group (19.9 ± 0.7 vs. 22.5 ± 1.9 μg/g tissue, p < 0.05). Plasma l-arginine, l-citrulline, and NOx levels were increased within 30 min after l-citrulline administration. EBD levels in the soleus and gastrocnemius muscles were higher in diabetic rats with l-citrulline administration (18.7 ± 2.2 vs. 25.0 ± 4.3 μg/g tissue, p < 0.05 and 8.0 ± 0.5 vs. 9.2 ± 0.8 μg/g tissue, p = 0.05, respectively). These data suggest that oral l-citrulline administration may increase the level of substances delivered to skeletal muscles by increasing the NO production in both normal and vascular endothelial dysfunction models.